Analyze Brand Ambassadors and Advertising Through Brand Image on Buyer Decisions: (Case Study: Purchase of BTS Meal at Mcdonald's Sukabumi) - Fauziah, Rossa Amalia; Siwiyanti, Leonita; Sudarma, Ade (The Es Economics and Entrepreneurship, 2024)
The purpose of this study is to see how advertising and brand representation influence consumer purchasing decisions, both directly and through brand image as a mediating variable. The background of the study was McDonald's strategic collaboration with BTS, which capitalized on the group's global popularity to attract customers through BTS Meal products. This phenomenon shows how marketing elements are crucial in influencing consumer behavior, especially children. This study used a quantitative approach with primary data collected through questionnaires. Respondents were customers who had purchased the BTS Meal at McDonald's Sukabumi. Structural Equation Model (SEM) was used to analyze the data. The study showed that advertising and brand ambassadors have a significant influence on the formation of brand image, which in turn affects consumers' decision to purchase goods. Advertising has a direct impact, but brand ambassadors do not. The implications of this study suggest companies should prioritise marketing strategies that utilise innovative and consistent advertising if they want to build a strong brand reputation. The right brand ambassador can enhance brand reputation, but to influence purchasing decisions directly, a more comprehensive strategy must be integrated. The results offer guidelines for other businesses to create successful marketing campaigns that utilise the synergy of branding elements to enhance brand appeal and increase consumer loyalty. To build stronger emotional connection with consumers, the study emphasises the importance of understanding the social and cultural dynamics of the target market.